2022
DOI: 10.3390/genes13091608
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Marrow HIV-Associated Hodgkin Lymphoma Complicated by Hemophagocytic Lymphohistiocytosis

Abstract: The presentation of human immunodeficiency virus (HIV)-associated Hodgkin lymphoma can differ from that of the general population. More specifically, primary bone marrow Hodgkin lymphoma is an uncommon presentation that is more often reported in patients with HIV. Given the many overlapping symptoms of Hodgkin lymphoma and HIV as well as HIV-associated infections, diagnosis can be difficult and delayed. We describe a case of primary bone marrow HIV-associated Hodgkin lymphoma complicated by hemophagocytic lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Further complicating the diagnoses is ferritin, being an inflammatory marker, can be elevated in both infection and HLH and has also been shown to be markedly elevated in patients with untreated/undiagnosed classic HL [ 4 ]. Our literature review found only two additional cases reporting PBMHL with HLH as a complication [ 6 , 7 ]. In those two cases and in our patient, HL in the bone marrow, along with the development of HLH, made this case challenging to manage and diagnose since the symptoms may overlap with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating the diagnoses is ferritin, being an inflammatory marker, can be elevated in both infection and HLH and has also been shown to be markedly elevated in patients with untreated/undiagnosed classic HL [ 4 ]. Our literature review found only two additional cases reporting PBMHL with HLH as a complication [ 6 , 7 ]. In those two cases and in our patient, HL in the bone marrow, along with the development of HLH, made this case challenging to manage and diagnose since the symptoms may overlap with each other.…”
Section: Discussionmentioning
confidence: 99%
“…As in some other cases described in the literature, the coincidence of HL in the bone marrow together with the development of HLH made this case difficult to manage and diagnose, since the symptoms may overlap with each other, making interpretation difficult [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%